(untitled) (Polish Yearbook of International Law, 2018)
In EU law a lot of attention has recently been paid to personal data protection standards. In parallel to the development of the general EU rules on data protection, the Members States also develop cooperation between law enforcement agencies and create new information exchange possibilities, including the processing of personal data of participants in criminal proceedings. The aim of this article is to analyse whether the personal data of victims of crime are safeguarded according to the standards of the Charter of Fundamental Rights. For this purpose, the author analyses two directives: 2012/29/EU, which regulates minimum standards of victims of crime; and 2016/680/EU (also known as the Law Enforcement Directive), which regulates personal data processing for the purpose of combating crime. Based on the example of the Polish legislation implementing both directives, the author comes to the conclusion that the EU legislation is not fully coherent and leaves too much margin of appreciation to the national legislator. This results in a failure to achieve the basic goals of both directives. The author expects the necessary reflection not only from the national legislator, but also from the European Commission, which should check the correctness of the implementation of the directives, as well as from national courts, which should use all possible measures to ensure that the national law is interpreted in the light of the objectives of the directives.